Saharan green corridors and Middle Pleistocene hominin dispersals across the Eastern Desert, Sudan. Issue 130 (May 2019) - Masojć, Mirosław; Nassr, Ahmed; Kim, Ju Yong; Krupa-Kurzynowska, Joanna; Sohn, Young Kwan; Szmit, Marcin; Kim, Jin Cheul; Kim, Ji Sung; Choi, Han Woo; Wieczorek, Małgorzata; Timmermann, Axel
Abstract: The Sahara Desert episodically became a space available for hominins in the Pleistocene. Mostly, desert conditions prevailed during the interpluvial periods, which were only periodically interrupted by enhanced precipitation during pluvial or interglacial periods. Responding to Quaternary climatic changes, hominin dispersal was channeled through vegetated corridors. This manuscript introduces a recently discovered group of Acheulean and Middle Stone Age sites far from the Nile Valley in the Eastern Desert (Sudan), referred to as Eastern Desert Atbara River (EDAR). The ∼5 m stratigraphy of the area is divided into three units (Units I–III) bounded by erosion surfaces. Each contains archaeological horizons. The EDAR area has rich surface sites with Acheulean horizons under the surface, singular finds of hand-axes within stratigraphic context in exposures, and large Acheulean sites partly exposed and destroyed by the gold mining activity. Optically stimulated luminescence (OSL) dating of Acheulean and MSA horizons from the EDAR 135 site indicates that the sedimentary deposits with stone artifacts were formed during the Middle Pleistocene between Marine Isotope Stages (MIS) 7 (pluvial) and 6 (interpluvial). Based on the OSL dating from the top of Unit IB, Acheulean artifact-bearing sedimentary deposits from overlying Unit IIA are younger than ca. 231 ka. Unit IA is the oldest Acheulean horizon in the EDAR area, not yet dated but definitively older than ca. 231 ka. An MSA horizon found in fluvial sediment was dated to be between 156 and 181 ka by OSL. The EDAR Pleistocene archaeological sites provide evidence for the presence of additional corridor(s) across Nubia, which connects the early hominin dispersals from the Nile and Atbara River systems to the Red Sea coast.